Analysis of the Effectiveness of HR Performance Measurement Using the Management by Objectives Approach at PT. Riseloka - Muhammad Salman Sepvian; Nining Kurnia; Rifal Hikmatul Fajri; Wasnia Safira (Jurnal Manajemen Bisnis dan Pariwisata, 2025)
This study aims to analyze the effectiveness of the implementation of Human Resources (HR) performance measurement at PT. Riseloka Bandung by using the Management by Objectives (MBO) approach. Data was collected through interviews with managers and employees, as well as analysis related to the evaluation of employee and team performance. The results showed that the implementation of MBO at PT. Riseloka gave positive results in improving HR performance, especially in setting clear, measurable, achievable, relevant, and strategy-based goals. However, there are some challenges such as goals that are sometimes too ambitious or less relevant to external conditions, less in-depth evaluation at some operational levels, and unequal access to development opportunities. This article concludesthat MBO is effective in managing and improving HR performance at PT. Riseloka, but requires continuous adjustment and improvement of feedback systems and development accessfor all employees for optimization.